Three-dimensional flow analysis of penta and ternary-hybrid nanofluids over an elongating sheet with thermal radiation and gyrotactic microorganisms - Davood Domiri Ganji; Mehdi Mahboobtosi; Fateme Nadalinia Chari (Scientific Reports)
Abstract This work studies the flow properties of a penta hybrid nanofluid and gyrotactic microorganism influence along an elongating surface. This study uniquely investigates the interaction of gyrotactic microorganisms with a penta-hybrid nanofluid (PHNF), marking a significant advancement over previous ternary hybrid nanofluid (THNF) models by introducing enhanced thermal and biological coupling through the inclusion of five distinct nanoparticles. The numerical solution is performed using MATLAB for the ODE equations. Convective boundary conditions are used to examine the rates of heat and mass transport, and the model incorporates external factors like magnetic fields and porous media. The Buongiorno model also takes into account the impact of Brownian motion and thermophoretic forces on the volumetric fraction of the nanoparticles. The results show that an increase in the magnetic parameter (M) and porous media factor (K) leads to a decrease in both the velocity profiles x and y velocity profile. An increase in K, however, increases the temperature, concentration, and microorganism profiles. On the other hand, an increase in the ratio parameter (α) increases the velocity profile in the y-direction but decreases the temperature, concentration, and microorganism profiles. Besides, larger radiation and Brownian motion parameters both lead to increased temperature profile, while the increased Brownian parameter leads to the decrease in the concentration profile. Surprisingly, PHNF is more effective than ternary hybrid nanofluid (THNF) and has superior thermal and mass transport characteristics. The optimisation of nanofluid and microbe applications, such as heat exchangers and biotechnological processes, where effective heat and mass transmission is essential, may benefit from these discoveries.